Pengaruh Lingkungan Kerja terhadap Kinerja Pegawai dengan Motivasi Intrinsik sebagai Variabel Intervening pada LPP RRI Kota Jambi - Novtria Rahmadani; Sumarni Sumarni; Nur Hasanah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to examine and analyze the influence of the work environment on employee performance through intrinsic motivation as an intervening variable on employees of LPP RRI (Radio Republik Indonesia) Jambi City. The method used is quantitative analysis with a population and sample of all employees totaling 74 respondents. Data were collected using a Likert scale-based questionnaire, and the analysis was carried out using the Structural Equation Modeling (SEM) technique based on Partial Least Square (PLS) with the help of SmartPLS 3 software. The results of the study indicate that: 1) the work environment has a positive and significant effect on employee performance, 2) the work environment has a positive and significant effect on intrinsic motivation, 3) intrinsic motivation has a positive and significant effect on employee performance, 4) intrinsic motivation as an intervening variable is able to mediate the influence of the work environment on employee performance positively and significantly.